2015
DOI: 10.7150/thno.10305
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MiR-16-5p and MiR-19b-3p as Two Novel Potential Biomarkers to Indicate Progression of Gastric Cancer

Abstract: Gastric cancer (GC) is the second most common cancer in China and the second leading cause of cancer-related death in the world. Identifying circulating biomarkers is helpful to improve theranostics of gastric cancer. Herein, we are for the first time to report miR-16-5p and miR-19b-3p were identified to be the novel potential plasma biomarkers to detect gastric cancer. Differentially expressed miRNAs were initially screened out by genome-wide miRNA profiling microarrays between 16 plasma samples of gastric ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 54 publications
7
109
1
Order By: Relevance
“…In addition, forced expression of miR-491-5p inhibited tumor proliferation, disrupted the cell cycle, and induced apoptosis in vitro and in vivo [49]. We also showed that lncRNA RP11-363E7.4 interacted with three miRNAs (miR-17-5p, miR-19b-3p, and miR-106a-5p), which were previously investigated in the reports of Xia et al, Zhang et al, and Qu et al [22,50,51]. …”
Section: Random Walk With Restart Analyses Of a Gc-related Lncrna-mrnmentioning
confidence: 49%
“…In addition, forced expression of miR-491-5p inhibited tumor proliferation, disrupted the cell cycle, and induced apoptosis in vitro and in vivo [49]. We also showed that lncRNA RP11-363E7.4 interacted with three miRNAs (miR-17-5p, miR-19b-3p, and miR-106a-5p), which were previously investigated in the reports of Xia et al, Zhang et al, and Qu et al [22,50,51]. …”
Section: Random Walk With Restart Analyses Of a Gc-related Lncrna-mrnmentioning
confidence: 49%
“…In our previous work, with the aim of finding early gastric cancer, we screen out some new biomarkers associated with early gastric cancer and develop novel ultrasensitive detection methods [8][9]. We also designed and fabricated some multifunctional nanoprobes for targeted imaging and simultaneous therapy of subcutaneous and in situ gastric cancer tissues with 5 mm in diameter [10][11][12][13][14][15][16][17][18][19][20][21][22]. Among those multifunctional nanoprobes, RGDconjugated gold nanorods could target tumor tissues and kill tumor cells via photothermal therapy [14], exhibiting potential clinical application prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Potential serum microRNA biomarkers included miR-187, miR-371-5p and miR-378, microRNA-21, miR-195, miRNA-206, MiR-16-5p and MiR-19b-3p. Serum miR-187, miR-371-5p and miR-378, microRNA-21, miR-627, miR-629 and miR-652 levels are positively related to gastric cancer while serum miR-195, miRNA-206, MiR-16-5p and MiR-19b-3p levels are negatively correlated with gastric cancer [76][77][78][79][80][81]. miR-378 alone could discriminate GC patients from healthy controls with 87.5% sensitivity and 70.73% specificity.…”
Section: Rna Markers Of Gastric Cancermentioning
confidence: 99%